Mobile Network Leader: A New Role of the Leader in Corporate Management = Mobilny lider sieci ? nowa rola menedżera w zarządzaniu firmą - Haber, Lesław H. (Zielona Góra: Faculty of Economics and Management Press)
The purpose of this paper was to present the management system evolution, from functional to process to network management. The network management system requires new organizational solutions associated with the fulfilment of external functions in management, directed at the acquisition of stakeholders from the environment who are treated as relational capital.
Keywords: sieciowy system zarządzania; lider zmian; mobilny lider sieci; moc sprawcza; kapitał relacyjny; network management systems; change leader; mobile network leader; causative power; Relational capital